LEAKAGE CURRENT ANALYSIS OF POLYMERIC INSULATION USING LINEAR TIME FREQUENCY DISTRIBUTION - NORDDIN, NURBAHIRAH; Abdullah, Abdul Rahim; Zainal Abidin, Nur Qamarina; Aman, Aminudin (2012)
Erosion on polymeric insulator surface caused by pollution affects their performance, until now there are no specific methods to determine their service life. Surface condition and their pollution severity of an insulator can be monitor by using leakage current frequency components. This paper presents time frequency distributions (TFD) for leakage current of polymeric insulation for high voltage applications. Tracking and erosion test (Inclined Plane Test (IPT)) complying with BS EN60587-2007 is conducted on polymeric insulation to collect different leakage current patterns. Since fast Fourier transforms (FFT) has limitation to analyze non stationary signal, thus time frequency distributions (TFD) shown in time frequency representation (TFR) with temporal and spectral is used. The verification using both methods on several disturbances signal with known parameters have been made and mean absolute percentage error (MAPE) used to identify the accuracy of both methods. The parameters measured are root mean square (RMS), total harmonic distortion (THD), total non harmonic distortion (TnHD) and total waveform distortion (TWD) used to determine the best method to analyze leakage current. The comparison shows that s-transform method is offer higher accuracy than spectrogram because it has better time and frequency resolution.